Conceptual Model for the Integration of PRONTO with ISO Standard 15926 - Sonzini, Maria Soledad (2013)
In this paper a conceptual model based on the ISO 15926 standard is proposed in order to extend and make explicit the representation of product variants given by PRONTO. This extension will allow introducing the product model in a collaborative environment where information systems are able to exchange information with other products systems. Interoperability of systems tends to increase the consistency of models, due to they may have several interpretations. Therefore, the proposal defines new elements and adapts these to the data model of the standard, for a complete concept mapping of PRONTO. Furthermore, changes in the product information are represented in time, through 4D approach.